Radioactive nuclei in the early Solar system: analysis of the 15 isotopes produced by core-collapse supernovae. Issue 1 (22nd December 2021) - Lawson, Thomas V; Pignatari, Marco; Stancliffe, Richard J; den Hartogh, Jacqueline; Jones, Sam; Fryer, Chris L; Gibson, Brad K; Lugaro, Maria
ABSTRACT: Short-lived radioactive isotopes (SLRs) with half-lives between 0.1 and 100 Myr can be used to probe the origin of the Solar system. In this work, we examine the core-collapse supernovae production of the 15 SLRs produced: 26 Al, 36 Cl, 41 Ca, 53 Mn, 60 Fe, 92 Nb, 97 Tc, 98 Tc, 107 Pd, 126 Sn, 129 I, 135 Cs, 146 Sm, 182 Hf, and 205 Pb. We probe the impact of the uncertainties of the core-collapse explosion mechanism by examining a collection of 62 core-collapse models with initial masses of 15, 20, and 25 M⊙, explosion energies between 3.4 × 10 50 and 1.8 × 10 52 erg and compact remnant masses between 1.5 and 4.89 M⊙ . We identify the impact of both explosion energy and remnant mass on the final yields of the SLRs. Isotopes produced within the innermost regions of the star, such as 92 Nb and 97 Tc, are the most affected by the remnant mass, 92 Nb varying by five orders of magnitude. Isotopes synthesized primarily in explosive C-burning and explosive He-burning, such as 60 Fe, are most affected by explosion energies. 60 Fe increases by two orders of magnitude from the lowest to the highest explosion energy in the 15 M⊙ model. The final yield of each examined SLR is used to compare to literature models.